Multi-dimensional combined polyanion sodium ion battery composite material
By adding graphene powder and carbon nanotubes to the polyanionic positive electrode material to form a three-dimensional conductive network, the structural collapse and electrolyte decomposition of existing sodium ion battery positive electrode materials in high-voltage environments is solved, and the electronic conductivity and rate performance are significantly improved, and the commercial application potential of the materials is enhanced.
Patent Information
- Application Number
- CN202510212814.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-11
AI Technical Summary
The existing sodium ion battery positive electrode materials are prone to structural collapse and electrolyte decomposition in high-voltage environments, resulting in performance attenuation and safety risks. The low electron conductivity and slow diffusion rate of sodium ions limit their commercial applications.
Using multi-dimensionally combined polyanionic sodium ion battery composite material, a three-dimensional conductive network is formed by adding graphene powder and carbon nanotubes to the polyanionic positive electrode material, which improves the electronic conductivity and improves the rate performance and cyclic stability of the material.
It significantly improves the electronic conductivity and rate performance of the material, reduces the volume expansion rate, enhances the electrochemical performance, and thus enhances the commercial application potential of the material.
Smart Images

Figure CN119812285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a multi-dimensionally combined polyanion sodium ion battery composite material. Background Art
[0002] In the field of sodium-ion batteries, the cathode material system is rich and diverse, covering Prussian blue and its analogs, transition metal oxides and polyanionic materials. Prussian blue and its analogs have shown good application potential due to their low cost, simple synthesis process, and high capacity and discharge voltage. However, due to the limitations of its liquid phase precipitation preparation process, coordinated lattice water is easily introduced into the material structure. These lattice waters are difficult to completely remove. Under high pressure, the lattice water will decompose to produce gas, causing battery failure, which greatly hinders the commercial application of this material.
[0003] Transition metal oxides also have the advantages of simple preparation process, high compaction density, and excellent rate performance. Their high discharge capacity and energy density have also attracted much attention. However, in practical applications, transition metal oxides will undergo complex phase changes during the sodium deintercalation process, which will cause structural collapse and cause serious performance degradation. In addition, under high pressure conditions, transition metal oxides are also prone to catalyze the decomposition of electrolytes to produce gas, which poses certain safety risks.
[0004] Polyanionic cathode materials (such as NaV2(PO4)3, Na2Fe2(SO4)3, etc.) have attracted much attention due to their stable three-dimensional skeleton structure and excellent thermal stability. However, their inherent low electronic conductivity (usually 10 -9 ~10 - ¹² S / cm) and slow sodium ion diffusion rate (10 -14 ~10 -16 cm² / s) leads to poor rate performance and short cycle life, which seriously restricts its commercial application.
[0005] Among the existing synthesis technologies, the solid phase method: the process is simple but the particles are severely agglomerated, resulting in obstruction of the ion diffusion path; the sol-gel method: the particle size can be controlled, but the cost is high, the cycle is long, and it is difficult to scale up; carbon coating technology: the carbon layer formed by the carbonization of traditional carbon black or sucrose is discontinuous, and the conductivity improvement is limited. On this basis, the uniformity of the material can be improved by adding a dispersant (such as a non-ionic surfactant), but the problem of insufficient conductivity has not been solved. In addition, although traditional carbon coating (such as conductive carbon black) can partially improve the conductivity, it is difficult to form a continuous conductive network, and the effect of regulating the material morphology is limited. Graphene has been used to construct a conductive network in lithium batteries. It has a large specific surface area and high conductivity, but it is easy to stack when used alone; carbon nanotubes (CNTs) have a one-dimensional structure that can bridge the gaps between particles and improve longitudinal conductivity, but their individual dispersion is poor. Summary of the invention
[0006] The invention aims to provide a multi-dimensionally combined polyanion sodium ion battery composite material, which has the characteristics of high electronic conductivity, good processability, low volume expansion rate and excellent electrochemical performance.
[0007] The present invention can be implemented by the following technical solutions:
[0008] The invention discloses a multi-dimensionally combined polyanion sodium ion battery composite material, comprising a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the addition amount of the graphene powder and the carbon nanotubes is 0.01-0.2 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax is less than 0.8 μm, and after drying, the solid particle size can be evenly distributed in the precursor powder; the two-dimensional graphene and the one-dimensional carbon nanotube form a certain three-dimensional network under the action of van der Waals force, are embedded between different particles, play the role of an electron transmission bridge between particles, shorten the migration distance of each element, and improve the phase purity; after the precursor is sintered at high temperature, the three-dimensional carbon structures are closely connected with the material crystal structure to form an effective electron transmission channel, greatly improve the electronic conductivity of the material, and then significantly improve the rate performance and cycle stability of the material.
[0009] The present invention uses two carbon materials, graphene and carbon nanotubes, both of which have high conductivity, large specific surface area and excellent mechanical properties, and can construct a three-dimensional conductive network, promote electron / ion transmission, and inhibit the volume expansion of the material during charging and discharging. Therefore, introducing graphene and carbon nanotubes into the polyanion positive electrode material system is an effective way to improve its electrochemical performance.
[0010] Furthermore, the graphene powder is one or more of single-layer graphene powder, single-layer graphene oxide, carboxylated graphene, reduced graphene oxide, polynitrogen-doped graphene, amino-modified graphene, sulfhydryl-modified graphene, and imidazole-modified graphene, and is a two-dimensional material composed of a single layer or a tightly stacked carbon atom with a honeycomb structure formed by sp2 hybridization of each carbon atom and three adjacent carbon atoms, and its modified products.
[0011] Furthermore, the carbon nanotubes are one or more of single-walled carbon nanotubes, fluorinated carbon nanotubes, whisker carbon nanotubes, nitrogen-doped multi-walled carbon nanotubes, graphitized carbon nanotubes, and amino-doped multi-walled carbon nanotubes, the carbon atoms are mainly sp2 hybridized, and the hexagonal grid structure has a certain degree of bending, forming a one-dimensional material with a spatial topological structure and its modified product.
[0012] Furthermore, the polyanionic positive electrode material is one or more of vanadium-based phosphate, iron-based phosphate, and manganese-based phosphate. The vanadium-based phosphate is one or more of Na3V2(PO4)3, Na3TiV(PO4)3, NaVPO4F and modified materials thereof. The iron-based phosphate is one or more of Na4Fe3(PO4)2P2O7, Na2Fe2(SO4)3, Na2FePO4F, NaFePO4 and modified materials thereof. The manganese-based phosphate is one or more of Na3MnTi(PO4)3, Na3MnZr(PO4)3, Na3MnV(PO4)3, Na3MnCr(PO4)3 and modified materials thereof.
[0013] Furthermore, the polyanion sodium ion battery is prepared by the following method: after the graphene powder and the carbon nanotubes are evenly mixed by wet method, the sodium source, the phosphorus source, the transition metal M source and the carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
[0014] Furthermore, the pH of the precursor solution is 2-10. Too high a pH value will cause the precursor to form a water-insoluble hydroxide precipitate. Controlling the pH of the precursor solution within a reasonable range has a strong correlation with the uniformity of the mixing of the elements in the early stage. The drying method is one or more of freeze drying, fluidized drying, forced air drying, reduced pressure drying, spray drying, and flash drying.
[0015] Furthermore, the conditions for high temperature sintering are: sintering temperature 500-730° C., sintering time 2-20 hours, and protective atmosphere of one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.
[0016] Furthermore, the carbon source is one or more of starch, lactic acid, oxalic acid, citric acid, malic acid, ascorbic acid, sucrose, glucose, adipic acid, and oxalic acid, and the added amount of the carbon source is 1-6wt% of the total solid content of the slurry.
[0017] Furthermore, the transition metal M source is one or more of a Fe source, a Mn source, and a V source, and the Fe source is Fe(OH)3, Fe(OH)2, Fe2O3, FeC2O4, FePO4, Fe(HCOO)2, Fe(HCOO)3, Fe(CH3COO)2, Fe(CH3COO)3, Fe(NO3) 3* 9H2O, Fe(NO3)2, FeSO4, one or more of the V source is NH4VO3, VO, V2O3, VO2, V2O5, and the Mn source is MnO, Mn2O3, Mn3O4, one or more of the Mn source.
[0018] Furthermore, the sodium source is one or more of Na3C6H5O7·2H2O, Na2SO4, NaNO3, Na2CO3, Na3PO4, Na4P2O7, Na2HPO4, Na2C2O4, NaH2PO4, CH3COONa, Na2H2P2O7, and HCOONa; the phosphorus source is one or more of sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, triammonium phosphate, pyrophosphoric acid, ammonium dihydrogen phosphate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
[0019] The multi-dimensionally combined polyanion sodium ion battery composite material of the present invention has the following beneficial effects:
[0020] First, the electronic conductivity is high. Under the action of van der Waals force, the carbon bodies of two-dimensional graphene and one-dimensional carbon nanotubes (CNTs) are connected to each other through active sites to form a certain three-dimensional network, which is in close contact with the material crystals and jointly constructs a three-dimensional continuous conductive network. Graphene has a high degree of graphitization (single layer rate>90%), and its planar structure provides a long-distance electron transmission path, and the electron mobility can reach 10 6 S / m. The one-dimensional tubular structure of carbon nanotubes bridges the gaps between particles to form a longitudinal conductive channel, and at the same time connects with graphene sheets through chemical bonds / physical adsorption to form a "point-line-surface" conductive network. Electrons are quickly transmitted along the graphene plane and conduct electricity across particles through CNTs, significantly reducing the internal resistance of the electrode and improving the rate performance;
[0021] Second, the processability is good. CNTs are interspersed in the gaps between the polyanion cathode material particles, and graphene wraps the particle surface. Through physical anchoring, a mechanical interlocking structure is formed to reduce particle shedding. The oxygen-containing functional groups on the surface of carboxylated CNTs form hydrogen bonds or van der Waals forces with the active substances to enhance the interface bonding. The amount of non-conductive binder used is reduced, the overall conductivity of the electrode is improved, and the manufacturing cost is reduced.
[0022] Third, the volume expansion rate is low. The high modulus of graphene and the toughness of CNT form an elastic buffer layer to fully absorb the charge and discharge stress; the conductive network promotes the uniform distribution of electrons, the normal deintercalation of sodium ions, reduces local polarization, and avoids stress concentration inside the particles. The carbon network structure inhibits particle pulverization and electrode structure collapse, thereby achieving the effect of inhibiting the destruction of the electrode structure caused by volume expansion.
[0023] Fourth, the electrochemical performance is excellent. The existence of the "point-line-surface" conductive network of graphene and carbon nanotubes reduces the polarization inside the material particles. During the charge and discharge process, the sodium is more evenly intercalated and deintercalated inside the material, the internal stress of the particles is smaller, and the degree of pulverization is reduced, which effectively improves the structural stability of the material under high-rate conditions, thereby improving its cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 For the Na3MnTi(PO4)3 / three-dimensional carbon material SEM in Application Example 1;
[0025] Figure 2 This is the SEM of Na3MnTi(PO4)3 / C material in Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0027] The invention discloses a multi-dimensionally combined polyanion sodium ion battery composite material, comprising a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the added amount of the graphene powder and the carbon nanotubes is 0.01-0.2 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax is less than 0.8 μm.
[0028] Furthermore, the graphene powder is one or more of single-layer graphene powder, single-layer graphene oxide, carboxylated graphene, reduced graphene oxide, polynitrogen-doped graphene, amino-doped graphene, sulfhydryl-doped graphene, and imidazole-modified graphene.
[0029] Furthermore, the carbon nanotubes are one or more of single-walled carbon nanotubes, fluorinated carbon nanotubes, whisker carbon nanotubes, nitrogen-doped multi-walled carbon nanotubes, graphitized carbon nanotubes, and amino-doped multi-walled carbon nanotubes.
[0030] Furthermore, the polyanionic positive electrode material is one or more of vanadium-based phosphate, iron-based phosphate, and manganese-based phosphate. The vanadium-based phosphate is one or more of Na3V2(PO4)3, Na3TiV(PO4)3, NaVPO4F and modified materials thereof. The iron-based phosphate is one or more of Na4Fe3(PO4)2P2O7, Na2Fe2(SO4)3, Na2FePO4F, NaFePO4 and modified materials thereof. The manganese-based phosphate is one or more of Na3MnTi(PO4)3, Na3MnZr(PO4)3, Na3MnV(PO4)3, Na3MnCr(PO4)3 and modified materials thereof.
[0031] Furthermore, the polyanion sodium ion battery is prepared by the following method: after the graphene powder and the carbon nanotubes are evenly mixed by wet method, the sodium source, the phosphorus source, the transition metal M source and the carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
[0032] Furthermore, the pH of the precursor solution is 2-10, and the drying method is one or more of freeze drying, fluidized bed drying, air drying, reduced pressure drying, spray drying, and flash drying.
[0033] Furthermore, the conditions for high temperature sintering are: sintering temperature 500-730° C., sintering time 2-20 hours, and protective atmosphere of one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.
[0034] Furthermore, the carbon source is one or more of starch, lactic acid, oxalic acid, citric acid, malic acid, ascorbic acid, sucrose, glucose, adipic acid, and oxalic acid, and the added amount of the carbon source is 1-6wt% of the total solid content of the slurry.
[0035] Furthermore, the transition metal M source is one or more of a Fe source, a Mn source, and a V source, and the Fe source is Fe(OH)3, Fe(OH)2, Fe2O3, FeC2O4, FePO4, Fe(HCOO)2, Fe(HCOO)3, Fe(CH3COO)2, Fe(CH3COO)3, Fe(NO3) 3* 9H2O, Fe(NO3)2, FeSO4, one or more of the V source is NH4VO3, VO, V2O3, VO2, V2O5, and the Mn source is MnO, Mn2O3, Mn3O4, one or more of the Mn source.
[0036] Furthermore, the sodium source is one or more of Na3C6H5O7·2H2O, Na2SO4, NaNO3, Na2CO3, Na3PO4, Na4P2O7, Na2HPO4, Na2C2O4, NaH2PO4, CH3COONa, Na2H2P2O7, and HCOONa; the phosphorus source is one or more of sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, triammonium phosphate, pyrophosphoric acid, ammonium dihydrogen phosphate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
[0037] Example 1
[0038] The present embodiment relates to a multi-dimensionally combined polyanion sodium ion battery composite material, comprising a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the added amount of graphene powder and carbon nanotubes is 0.2 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax<0.8μm.
[0039] In this embodiment, the graphene powder is single-layer graphene powder or single-layer graphene oxide; the carbon nanotube is single-walled carbon nanotube, fluorinated carbon nanotube or whisker carbon nanotube; the polyanionic positive electrode material is vanadium-based phosphate or iron-based phosphate, the vanadium-based phosphate is Na3V2(PO4)3 or Na3TiV(PO4)3, and the iron-based phosphate is Na4Fe3(PO4)2P2O7.
[0040] In this embodiment, the polyanion sodium ion battery is prepared by the following method: after the graphene powder and carbon nanotubes are evenly mixed by wet method, the sodium source, phosphorus source, transition metal M source and carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
[0041] Specifically, the pH of the precursor solution is 2-10, and the drying method is freeze drying; the conditions for high-temperature sintering are: sintering temperature 730° C., sintering time 10 hours, and protective atmosphere nitrogen and argon.
[0042] In terms of raw materials, the carbon sources are starch, lactic acid, and oxalic acid, and the amount of carbon source added is 6wt% of the total solid content of the slurry; the transition metal M sources are Fe sources and V sources, the Fe sources are Fe(OH)3, Fe(OH)2, and Fe2O3, and the V sources are NH4VO3, VO, V2O3, VO2, and V2O5; the sodium sources are Na3C6H5O7·2H2O and Na2SO4; the phosphorus sources are sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and phosphoric acid.
[0043] Example 2
[0044] The present embodiment relates to a multi-dimensionally combined polyanion sodium ion battery composite material, comprising a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the added amount of graphene powder and carbon nanotubes is 0.1 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax<0.8μm.
[0045] In this embodiment, the graphene powder is polynitrogen-doped graphene, amino-doped graphene, hydrophobic graphene, and imidazole-modified graphene; the carbon nanotubes are graphitized carbon nanotubes and amino-doped multi-walled carbon nanotubes; the polyanionic positive electrode material is manganese-based phosphate, and the manganese-based phosphate is Na3MnTi(PO4)3, Na3MnZr(PO4)3 and its modified materials.
[0046] In this embodiment, the polyanion sodium ion battery is prepared by the following method: after the graphene powder and carbon nanotubes are evenly mixed by wet method, the sodium source, phosphorus source, transition metal M source and carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
[0047] Specifically, the pH of the precursor solution is 6, and the drying method is fluidized drying and forced air drying; the conditions for high-temperature sintering are: sintering temperature 630° C., sintering time 2 h, and protective atmosphere argon.
[0048] In terms of raw materials, the carbon sources are glucose, adipic acid, and oxalic acid, and the amount of carbon source added is 3wt% of the total solid content of the slurry; the transition metal M source is Mn source, and the Mn source is MnO and Mn2O3; the sodium source is CH3COONa, Na2H2P2O7, and HCOONa; the phosphorus source is disodium hydrogen phosphate, phosphoric acid, triammonium phosphate, and pyrophosphoric acid.
[0049] Example 3
[0050] The present embodiment relates to a multi-dimensionally combined polyanion sodium ion battery composite material, comprising a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the added amount of graphene powder and carbon nanotubes is 0.2 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax<0.8μm.
[0051] In this embodiment, the graphene powder is single-layer graphene powder, single-layer graphene oxide, and imidazole-modified graphene. The carbon nanotubes are single-walled carbon nanotubes and amino-modified multi-walled carbon nanotubes; the polyanion-type positive electrode material is iron-based phosphate and manganese-based phosphate, the iron-based phosphate is Na4Fe3(PO4)2P2O7 and its modified materials, and the manganese-based phosphate is Na3MnTi(PO4)3, Na3MnZr(PO4)3 and its modified materials.
[0052] In this embodiment, the polyanion sodium ion battery is prepared by the following method: after the graphene powder and carbon nanotubes are evenly mixed by wet method, the sodium source, phosphorus source, transition metal M source and carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
[0053] Specifically, the pH of the precursor solution is 2, and the drying method is spray drying; the conditions for high-temperature sintering are: sintering temperature 500° C., sintering time 20 hours, and protective atmosphere of nitrogen and hydrogen.
[0054] In terms of raw materials, the carbon sources are starch, lactic acid, oxalic acid, citric acid, adipic acid, and oxalic acid, and the amount of carbon source added is 1wt% of the total solid content of the slurry; the transition metal M sources are Fe source and Mn source, the Fe source is Fe(OH)3, Fe(OH)2, Fe2O3, and the Mn source is MnO and Mn3O4; the sodium source is Na3C6H5O7·2H2O; the phosphorus source is sodium phosphate, sodium monohydrogen phosphate, and sodium dihydrogen phosphate.
[0055] Example 4
[0056] The present embodiment relates to a multi-dimensionally combined polyanion sodium ion battery composite material, comprising a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the added amount of graphene powder and carbon nanotubes is 0.13 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax<0.8μm.
[0057] In this embodiment, the graphene powder is carboxylated graphene, reduced graphene oxide, sulfhydrylated graphene, and imidazole-modified graphene. The carbon nanotubes are single-walled carbon nanotubes, nitrogen-doped multi-walled carbon nanotubes, graphitized carbon nanotubes, and amino-modified multi-walled carbon nanotubes. The polyanion-type positive electrode material is an iron-based phosphate, and the iron-based phosphate is Na4Fe3(PO4)2P2O7 or Na2Fe2(SO4)3.
[0058] In this embodiment, the polyanion sodium ion battery is prepared by the following method: after the graphene powder and carbon nanotubes are evenly mixed by wet method, the sodium source, phosphorus source, transition metal M source and carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
[0059] Specifically, the pH of the precursor solution is 2-10, and the drying method is forced air drying; the conditions for high-temperature sintering are: sintering temperature 600° C., sintering time 12 hours, and protective atmosphere argon hydrogen.
[0060] In terms of raw materials, the carbon sources are starch, lactic acid, oxalic acid, and citric acid, and the amount of carbon source added is 2wt% of the total solid content of the slurry; the transition metal M source is Fe source, and the Fe source is Fe(OH)3, Fe(OH)2, and Fe2O3; the sodium source is Na3C6H5O7·2H2O and Na2SO4; and the phosphorus source is sodium dihydrogen pyrophosphate.
[0061] Example 5
[0062] The present embodiment relates to a multi-dimensionally combined polyanion sodium ion battery composite material, comprising a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the added amount of graphene powder and carbon nanotubes is 0.06 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax<0.8μm.
[0063] In this embodiment, the graphene powder is single-layer graphene powder or single-layer graphene oxide; the carbon nanotube is single-walled carbon nanotube, fluorinated carbon nanotube, whisker carbon nanotube, or nitrogen-doped multi-walled carbon nanotube; the polyanionic positive electrode material is iron-based phosphate, and the iron-based phosphate is Na4Fe3(PO4)2P2O7.
[0064] In this embodiment, the polyanion sodium ion battery is prepared by the following method: after the graphene powder and carbon nanotubes are evenly mixed by wet method, the sodium source, phosphorus source, transition metal M source and carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
[0065] Specifically, the pH of the precursor solution is 7, and the drying method is flash drying; the conditions for high-temperature sintering are: sintering temperature 530° C., sintering time 15 h, and protective atmosphere nitrogen and argon.
[0066] In terms of raw materials, the carbon sources are starch, lactic acid, and oxalic acid, and the amount of carbon source added is 5wt% of the total solid content of the slurry; the transition metal M source is Fe source, and the Fe source is Fe(CH3COO)2 and Fe(CH3COO)3; the sodium source is Na3C6H5O7·2H2O, Na2SO4, NaNO3, Na2CO3; the phosphorus source is sodium phosphate, pyrophosphoric acid, ammonium dihydrogen phosphate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
[0067] Application Example 1 Synthesis and electrochemical performance of Na3MnTi(PO4)3 / three-dimensional carbon materials
[0068] This embodiment relates to Na3MnTi(PO4)3 / three-dimensional carbon material, and its preparation method comprises the following steps:
[0069] Step 1: Mix the monolayer graphene oxide (the addition amount is 1.2wt% of the total solid content of the slurry) and the whisker carbon nanotube (the addition amount is 3.6wt% of the total solid content of the slurry) with water, and grind them with a sand mill for 2 hours to form a uniform black emulsion;
[0070] Step 2: Weigh Mn2O3, TiO2 and NaH2PO4 according to the stoichiometric ratio of 0.5:1:3 in the molecular formula and add them to the above emulsion, use glucose as a carbon source (the addition amount is 3.6% of the total solid content of the slurry), disperse and dissolve them to form a uniform black precursor solution;
[0071] Step 3: spray drying the precursor solution at an air inlet temperature of 310° C. and an air outlet temperature of 105° C. to remove moisture and obtain a dry precursor powder;
[0072] Step 4: In a nitrogen atmosphere, keep the precursor powder at 630°C for 11 hours, and then cool it down naturally to obtain Na3MnTi(PO4)3 / three-dimensional carbon material.
[0073] Figure 1This is the SEM image of Na3MnTi(PO4)3 / three-dimensional carbon material, which is spherical particles of about 2um. The particle distribution is relatively uniform, and there are no obvious large particle aggregates. In addition, a large amount of three-dimensional carbon network material is distributed outside the spherical structure. The carbon structure is evenly distributed outside the sphere and interconnected with other particles to form an effective conductive network, which is beneficial to improving the electronic conductivity and structural stability of the material.
[0074] After Na3MnTi(PO4)3 / three-dimensional carbon, acetylene black, and polyvinylidene fluoride were mixed into a slurry at a mass ratio of 7:2:1, the black slurry was coated on aluminum foil using a 140um four-sided preparation device, and then the film was dried in a vacuum drying oven at 110°C for 1.5 hours. The electrode film was punched into a disc with a radius of 0.5mm using a punching machine, with metal Na as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.
[0075] The button cell was subjected to constant current charge and discharge test with a current density of 0.1C (1C=120mAh / g). As shown in Table 1, under the condition of 0.1C rate, the material exhibited a reversible capacity of 101.2mAh / g, which is slightly higher than the 97.9mAh / g of Comparative Example 1. The generation of this performance advantage is closely related to the presence of a three-dimensional carbon mesh structure in the material. Both graphene and carbon nanotubes have high electronic conductivity, which can make the polarization process inside / outside the material particles more uniform, so that the capacity of the material can be effectively exerted. In terms of rate performance, the capacity retention rates of the material at 2C and 5C rates reached 98.8% and 97.2%, respectively, which are significantly higher than 93.3% and 92.3% of Comparative Example 1 under the same test conditions, showing a more excellent rate performance. This fully demonstrates that after the introduction of carbon fiber into the material, the electronic conductivity between the material particles is significantly improved, thereby effectively improving the rate performance of the material. In addition, the results of the cycle stability test showed that after 1000 cycles at 1C and 5C rates, the capacity retention rates of the material were 98.7% and 97.2%, respectively, showing better cycle stability than Comparative Example 1. This is mainly attributed to the three-dimensional carbon structure that increases the structural stability of the material and effectively reduces the powder loss problem that occurs during the sodium insertion and extraction process.
[0076] Application Example 2 Synthesis and Electrochemical Performance of Na4Fe3(PO4)2P2O7 / Three-Dimensional Carbon Materials
[0077] This embodiment relates to Na4Fe3(PO4)2P2O7 / three-dimensional carbon material, and its preparation method comprises the following steps:
[0078] Step 1: Carboxylated graphene (added in an amount of 1.2 wt% of the total solid content of the slurry) and nitrogen-doped multi-walled carbon nanotubes (added in an amount of 3.6 wt% of the total solid content of the slurry) were mixed with water and ground with a sand mill for 2 hours to form a uniform black emulsion;
[0079] Step 2: Fe(NO3) 3* 9H2O, NaH2PO4, and CH3COONa are weighed according to the stoichiometric ratio in the molecular formula and added to the above emulsion, and sucrose is used as a carbon source (the addition amount is 2.9% of the total solid content of the slurry), dispersed and dissolved to form a uniform black precursor solution;
[0080] Step 3: spray drying the precursor solution at an air inlet temperature of 300° C. and an air outlet temperature of 101° C. to remove moisture and obtain a dry precursor powder;
[0081] Step 4: In a nitrogen atmosphere, keep the precursor powder at 600°C for 15 hours, and then cool naturally to obtain Na4Fe3(PO4)2P2O7 / three-dimensional carbon material.
[0082] After Na4Fe3(PO4)2P2O7 / three-dimensional carbon, acetylene black, and polyvinylidene fluoride were mixed into a slurry at a mass ratio of 7:2:1, the slurry was evenly coated on aluminum foil using a 140um four-sided preparation device, and then the film was placed in a vacuum drying oven at 110°C and dried for 1.5 hours. The electrode film was punched into a disc with a radius of 0.5mm using a punching machine, with metal Na as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.
[0083] The button cell was subjected to constant current charge and discharge test with a current density of 0.1C (1C=129mAh / g). As shown in Table 1, under the condition of 0.1C rate, the material exhibited a reversible capacity of 98.7mAh / g, which is higher than the 94.2mAh / g of Comparative Example 2. The generation of this performance advantage is closely related to the presence of a three-dimensional carbon mesh structure in the material. Both graphene and carbon nanotubes have high electronic conductivity, which can make the polarization process inside / outside the material particles more uniform, so that the capacity of the material can be effectively exerted. In terms of rate performance, the capacity retention rates of the material at 2C and 5C rates reached 95.3% and 94.7%, respectively, which are significantly higher than 93.7% and 92.8% of Comparative Example 2 under the same test conditions, showing a more excellent rate performance. This fully demonstrates that after the three-dimensional carbon structure is introduced into the material, the electronic conductivity between the material particles is significantly improved, thereby effectively improving the rate performance of the material. In addition, the results of the cycle stability test showed that after 1000 cycles at 1C and 5C rates, the capacity retention rates of the material were 92.3% and 84.5%, respectively, which showed better cycle stability than Comparative Example 2. This is mainly attributed to the fact that the three-dimensional carbon structure increases the structural stability of the material and effectively reduces the powder loss problem during the sodium insertion and extraction process.
[0084] Comparative Example 1 Synthesis and electrochemical performance of Na3MnTi(PO4)3 / C
[0085] This embodiment relates to Na3MnTi(PO4)3 / C, and its preparation method comprises the following steps:
[0086] Step 1: Glucose as a carbon source (the addition amount is 3.6% of the total solid content of the slurry), Mn2O3, TiO2 and NaH2PO4 are weighed according to the stoichiometric ratio of 0.5:1:3 in the molecular formula and added into deionized water for dispersion and dissolution to form a uniform precursor solution;
[0087] Step 2: spray drying the above precursor solution, with an air inlet temperature of 310°C and an air outlet temperature of 105°C, to remove moisture and obtain a dry precursor powder;
[0088] Step: 3: In a nitrogen atmosphere, keep the precursor powder at 630°C for 11 hours, and then cool it down naturally to obtain Na3MnTi(PO4)3 / C.
[0089] Figure 2 This is the SEM image of Na3MnTi(PO4)3 / C material, which is composed of spherical particles of about 3~5um. The larger spherical particles are related to the agglomeration and unevenness during the sand grinding process of the raw materials. Figure 2This is the XRD of Na3MnTi(PO4)3 material. The diffraction intensity of this material is low, and there are many impurity diffraction peaks, indicating that the material has poor crystallinity and phase separation, which is related to the poor uniformity of dispersion between elements and the existence of agglomeration.
[0090] After Na3MnTi(PO4)3, acetylene black and polyvinylidene fluoride were mixed into a slurry at a mass ratio of 7:2:1, the black slurry was coated on aluminum foil using a 140um four-sided preparation device, and then the film was dried in a vacuum drying oven at 110°C for 1.5 hours. The electrode film was punched into a disc with a radius of 0.5mm using a punching machine, with metal Na as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.
[0091] The above button cell was subjected to constant current charge and discharge test, and the current density was 0.1C (1C=120mAh / g). The results in Table 1 show that the reversible capacity of the material at a rate of 0.1C is 97.9mAh / g, which is lower than 101.2mAh / g in Application Example 1. The reason for the low capacity is related to the low electronic conductivity of the material, which will aggravate the polarization during the charge and discharge process to a certain extent, resulting in abnormal performance of the material capacity inside some particles. The capacity retention rates of the material at 2C and 5C rates are 94.1% and 93.3%, respectively, which are lower than those in Application Example 1 under the same conditions, showing poor rate performance, indicating that the material has a large internal resistance. In addition, the material has a capacity retention rate of 92.3% and 84.5% after 1000 cycles at 1C and 5C rates, respectively, which shows poor cycle stability compared to Application Example 1, which is related to the lack of three-dimensional carbon coating on the material, resulting in poor structural stability, and the problem of powdering during the sodium deintercalation process.
[0092] Comparative Example 2 Synthesis and Electrochemical Performance of Na4Fe3(PO4)2P2O7 / C
[0093] This embodiment relates to Na4Fe3(PO4)2P2O7 / C, and its preparation method comprises the following steps:
[0094] Step 1: Sucrose as carbon source (added at 2.9% of the total solid content of the slurry), Fe(NO3) 3* 9H2O, NaH2PO4, and CH3COONa are weighed according to the stoichiometric ratio in the molecular formula and added to the above emulsion to disperse and dissolve to form a uniform precursor solution;
[0095] Step 2: spray drying the above precursor solution, with an air inlet temperature of 300°C and an air outlet temperature of 101°C, to remove moisture and obtain a dry precursor powder;
[0096] Step: 3: In a nitrogen atmosphere, keep the precursor powder at 600°C for 15 hours, and then cool it down naturally to obtain Na4Fe3(PO4)2P2O7 / C material.
[0097] After Na4Fe3(PO4)2P2O7 / C, acetylene black and polyvinylidene fluoride were mixed into a slurry at a mass ratio of 7:2:1, the slurry was evenly coated on aluminum foil using a 140um four-sided preparation device, and then the film was placed in a vacuum drying oven at 110°C for 1.5 hours. The electrode film was punched into a disc with a radius of 0.5mm using a punching machine, with metal Na as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.
[0098] The above button cell was subjected to constant current charge and discharge test, and the current density was 0.1C (1C=129mAh / g). The results in Table 1 show that the reversible capacity of the material at a rate of 0.1C is 94.2mAh / g, which is lower than 98.7mAh / g in Application Example 1. The reason for the low capacity is related to the low electronic conductivity of the material, which will aggravate the polarization during the charge and discharge process to a certain extent, resulting in abnormal performance of the material capacity inside some particles. The capacity retention rates of the material at 2C and 5C rates are 93.7% and 92.8%, respectively, which are lower than those in Application Example 2 under the same conditions, showing poor rate performance, indicating that the material has a large internal resistance. In addition, the material has a capacity retention rate of 91.4% and 83.6% after 1000 cycles at 1C and 5C rates, respectively, which shows poor cycle stability compared to Application Example 2, which is related to the lack of three-dimensional carbon coating of the material, and the cycle stability is severely attenuated due to the poor stability of the structure.
[0099] Table 1 Performance test results
[0100] Application Example 1 Comparative Example 1 Application Example 2 Comparative Example 2 0.1C discharge specific capacity (mAh / g) 101.2 97.9 98.7 94.2 Rate performance 2C (%) 98.8 94.1 95.3 93.7 Rate performance 5C (%) 97.2 93.3 94.7 92.8 Capacity retention rate after 1000 cycles at 1C (%) 98.7 92.3 97.2 91.4 Capacity retention rate after 1000 cycles at 5C (%) 97.2 84.5 96.7 83.6
[0101] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A multi-dimensionally combined polyanion sodium ion battery composite material, characterized in that: It comprises a polyanion positive electrode material, graphene powder and carbon nanotubes, wherein the added amount of the graphene powder and the carbon nanotubes is 0.01-0.2 of the molar amount of the polyanion positive electrode material; in the polyanion sodium ion battery composite material, the solid particle size Dmax is less than 0.8 μm.
2. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 1, characterized in that: The graphene powder is one or more of single-layer graphene powder, single-layer graphene oxide, carboxylated graphene, reduced graphene oxide, polynitrogen-doped graphene, amino-doped graphene, sulfhydryl-doped graphene, and imidazole-modified graphene.
3. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 1, characterized in that: The carbon nanotubes are one or more of single-walled carbon nanotubes, fluorinated carbon nanotubes, whisker carbon nanotubes, nitrogen-doped multi-walled carbon nanotubes, graphitized carbon nanotubes, and amino-doped multi-walled carbon nanotubes.
4. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 1, characterized in that: The polyanion positive electrode material is one or more of vanadium-based phosphate, iron-based phosphate and manganese-based phosphate. The vanadium-based phosphate is one or more of Na3V2(PO4)3, Na3TiV(PO4)3, NaVPO4F and modified materials thereof. The iron-based phosphate is one or more of Na4Fe3(PO4)2P2O7, Na2Fe2(SO4)3, Na2FePO4F, NaFePO4 and modified materials thereof. The manganese-based phosphate is one or more of Na3MnTi(PO4)3, Na3MnZr(PO4)3, Na3MnV(PO4)3, Na3MnCr(PO4)3 and modified materials thereof.
5. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 1, characterized in that: The polyanion sodium ion battery is prepared by the following method: after the graphene powder and the carbon nanotubes are uniformly mixed by wet method, a sodium source, a phosphorus source, a transition metal M source and a carbon source are dissolved to form a precursor solution, and after drying, high-temperature sintering is performed to form a polyanion sodium ion battery composite material.
6. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 5, characterized in that: The pH of the precursor solution is 2-10, and the drying method is one or more of freeze drying, fluidized drying, blast drying, reduced pressure drying, spray drying, and flash drying.
7. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 6, characterized in that: The conditions for high-temperature sintering are: sintering temperature 500-730° C., sintering time 2-20 hours, and protective atmosphere of one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.
8. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 7, characterized in that: The carbon source is one or more of starch, lactic acid, oxalic acid, citric acid, malic acid, ascorbic acid, sucrose, glucose, adipic acid, and oxalic acid, and the added amount of the carbon source is 1-6wt% of the total solid content of the slurry.
9. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 8, characterized in that: The transition metal M source is one or more of a Fe source, a Mn source, and a V source; the Fe source is Fe(OH)3, Fe(OH)2, Fe2O3, FeC2O4, FePO4, Fe(HCOO)2, Fe(HCOO)3, Fe(CH3COO)2, Fe(CH3COO)3, Fe(NO3) 3* 9H2O, Fe(NO3)2, FeSO4, one or more of the V source is NH4VO3, VO, V2O3, VO2, V2O5, and the Mn source is MnO, Mn2O3, Mn3O4, one or more of the Mn source.
10. The multi-dimensionally combined polyanion sodium ion battery composite material according to claim 9, characterized in that: The sodium source is one or more of Na3C6H5O7·2H2O, Na2SO4, NaNO3, Na2CO3, Na3PO4, Na4P2O7, Na2HPO4, Na2C2O4, NaH2PO4, CH3COONa, Na2H2P2O7, and HCOONa; the phosphorus source is one or more of sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, triammonium phosphate, pyrophosphoric acid, ammonium dihydrogen phosphate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
Citation Information
Cited By
Polyanion composite positive electrode material and preparation method thereof
CN120978049A